How and why do participatory women's groups (PWGs) improve the quality of maternal and child health (MCH) care? A systematic review protocol. Issue 9 (5th September 2019) - Preston, Robyn; Rannard, Sam; Felton-Busch, Catrina; Larkins, Sarah; Canuto, Karla; Carlisle, Karen; Evans, Rebecca; Redman-MacLaren, Michelle; Taylor, Judy; Turner, Nalita Nungarrayi; Yeomans, Lee; Sanguineti, Emma; et al.
Abstract : Introduction: Community-based Participatory Women's Groups (PWGs) have proven to be an effective intervention to improve maternal and child health (MCH) outcomes in low/middle-income countries (LMICs). Less is known about how PWGs exert their effects in LMICs and virtually nothing is known about the contextual issues, processes and power relationships that affect PWG outcomes in high resource settings. The aim of this systematic review is to synthesise and critically analyse the current evidence on how and why PWGs improve the quality of MCH care. We aim to demonstrate how PWGs function and why PWG interventions contribute to social and health outcomes. Methods and analysis: The protocol will follow Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. The databases Medline (Ovid): Cumulative Index to Nursing and Allied Health Literature (Ebsco); Informit health suite Scopus, Australian HealthInfoNet, the Cochrane Library and other sources will be searched under broad categories: intervention, context and outcomes to 30 June 2019. Ethics and dissemination: As only secondary data will be analysed; ethical approval is not required. The review will be disseminated to relevant organisations and presented in peer-reviewed papers and at conferences. This will be the first attempt to summarise the current available evidence on the characteristics, contextual influences and mechanisms that are associated with the outcomes and effectiveness of PWGs. PROSPERO registration number: CRD42019126533.